Combination of chemical etching of gold nanoclusters with aggregation-induced emission for preparation of new phosphors for the development of UV-driven phosphor-converted white light-emitting diodes. Issue 48 (25th November 2016) - Lu, Xin; Wang, Tao; Shu, Tong; Qu, Xuanhui; Zhang, Xueji; Liang, Feng; Su, Lei
Abstract : The preparation of white light-emitting phosphors via TECP-induced etching of GNCs@BSA and Cd 2+ -induced aggregation, followed by grinding with GNCs@BSA. Abstract : In this study, a combination of chemical etching of gold nanoclusters with the aggregation-induced emission (AIE) effect to prepare luminescent organic solid materials for the development of UV-driven phosphor-converted white light-emitting diodes (pc-WLEDs) has been demonstrated for the first time. Bovine serum albumin-capped gold nanoclusters (GNCs@BSA) are etched by tris(2-carboxyethyl)phosphine (TCEP), followed by cadmium ion-induced aggregation, which converts them to multiple phosphor powders that show a continuous emission spectrum in the range of blue light to yellow light. The resultant aggregates could be separated from the blue light-emitting protein components via ultrafiltration, and are responsible for the yellow-green light spectral component. In addition, the as-prepared multiple phosphor powders show mechanochromic luminescent properties. The as-prepared multiple phosphor powders supplemented with red-emissive GNCs@BSA could be used as the white light generating layer of commercial GaN UV LEDs, and the generated white light could be suitable for indoor lighting. In addition, this study reveals that the AIE properties of the cadmium ion-induced aggregated Au(i ) complexes can be tailored by organic etchants. Such tunability could indicate the promising potential of chemically etched GNCs as a new means for the design of aggregation-induced emissive Au(i ) complexes for the development of new phosphors for white UV-LED applications.